2021
DOI: 10.1212/wnl.0000000000012147
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage, Limited-Resection Epilepsy Surgery for Bottom-of-Sulcus Dysplasia

Abstract: Objective:To determine if one-stage, limited corticectomy controls seizures in patients with MRI-positive, bottom-of-sulcus dysplasia (BOSD).Methods:We reviewed clinical, neuroimaging, electrocorticography (ECoG), operative and histopathology findings in consecutively operated patients with drug-resistant focal epilepsy and MRI-positive BOSD, all of whom underwent corticectomy guided by MRI and ECoG.Results:38 patients with median age at surgery of 10.2 (IQR: 6.0-14.1) years were included. BOSDs involved eloqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 50 publications
(78 reference statements)
1
50
0
Order By: Relevance
“…FCDII subtypes became much better characterized as clinical entities with well‐defined EEG signatures in FCDIIa and IIb subtypes. The specificity of interictal patterns such as focal continuous rhythmic discharges and repetitive spiking have been suggested as possible predictors of the ictal‐onset zone and of favorable postresection seizure outcome 3,18,26–29 . Previous studies have shown that intrinsic epileptogenicity might not overlap with the MRI‐observed abnormality 30,31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FCDII subtypes became much better characterized as clinical entities with well‐defined EEG signatures in FCDIIa and IIb subtypes. The specificity of interictal patterns such as focal continuous rhythmic discharges and repetitive spiking have been suggested as possible predictors of the ictal‐onset zone and of favorable postresection seizure outcome 3,18,26–29 . Previous studies have shown that intrinsic epileptogenicity might not overlap with the MRI‐observed abnormality 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…They tend to localize in the depth of frontal lobe sulci (superior frontal sulcus, inferior frontal sulcus, and central sulcus) and less frequently in the parietal or temporal lobes. Direct intralesional, intraoperative, or extraoperative depth electrode electroencephalography (EEG) recordings identify a characteristic rhythmic spiking pattern in the depth of sulcus lesion 16,18 . The complete resection of the anatomic lesion achieves seizure freedom in most patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…iECoG guides resection by IED activity, which can better delineate the affected region in FCD 48 . This may be because cortical dysplastic brain, particularly Type II FCD, may be a driver of peri‐ and intralesional interictal continuous spikes, and thus when resected under iECoG, could correlate with seizure freedom 14,49,50 . Although iECoG‐based FCD resection, regardless of subtype, shows improvement in seizure freedom, 51,52 FCD subtypes associated with lesional pathology (Type III) have shown the best postoperative seizure freedom 20,52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Specific examples of high-risk surgery illustrating our clinical learning curve with Karawun include our previously reported one-stage, language dominant, insular-opercular epilepsy surgery series, and the related bottom-of-sulcus-dysplasia (BOSD) epilepsy surgery series, representing over 10 years of our clinical experience, performed with advanced fMRI and tractography guidance [ 35 , 36 ]. We demonstrated excellent surgical and seizure outcomes in both surgical series, without the need to perform additional invasive procedures for functional brain mapping, including in an awake craniotomy setting, which is unsuited for the majority of children.…”
Section: Discussionmentioning
confidence: 99%